THE ANALYSIS OF FACTORS AFFECTING THE VALUE OF COMPANY WITH DEBT POLICY AS INTERVENING VARIABLES (STUDY IN MANUFACTURING COMPANIES LISTED ON IDX) - Rambe, Bhakti Helvi (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research is to analyze some factors which influenced the firm's value with debt. The company is listed in the Indonesia Stock Exchange in the period of 2014-2017. The research used causal method. The population was 144 companies, and 45 of them were used as the samples, taken by using purposive sampling technique, so that there would be 180 observation units. The data were analyzed by using multiple linear regression analysis and path analysis. The result of the research showed that, simultaneously, Profitability, Firm Size, Free Cash Flow (FCF), Sales Growth, and Investment Opportunity Set (IOS) had significant influence on firm value. Partially, the variables of Profitability and Firm Size have positive and significant influence on firm value, Free Cash Flow (FCF), Sales Growth, and Investment Opportunity Set (IOS) have positive but insignificant influence on firm value. Debt to Equity Ratio (DER) has negative influence on firm value. Simultaneously, Profitability, Firm Size, Free Cash Flow (FCF), Sales Growth, and Investment Opportunity Set (IOS) Investment Opportunity Set (IOS) Partially, the variables of Profitability and Firm Size have positive influence on Free Cash Flow ( FCF), Sales Growth has a positive but insignificant influence on Debt to Equity Ratio (DER). Meanwhile, Investment Opportunity Set (IOS) has negative influence on Debt to Equity Ratio (DER), while Debt to Equity Ratio (DER) could not mediate the correlation of Profitability, Firm Size, Free Cash Flow (FCF), Sales Growth, and Investment Opportunity Set (IOS) with Firm Value.